2019
DOI: 10.32585/jdb.v2i2.373
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruhcontextual Teaching and Learningterhadap Motivasi Belajar Dan Keterampilan Berpikir Kritis

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh pendekatan Contextual Teaching and Learning (CTL) terhadap motivasi belajar dan keterampilan berpikir kritis siswa kelas IV tema 8 daerah tempat tinggalku di SDN 2 Klapasawit. Metode penelitian menggunakan Quasy Eksperimen dengan desain penelitian Nonequivalent (pretest-posttest) Control Group Design. Populasi penelitian adalah siswa kelas IV SDN 2 Klapasawit berjumlah 47 siswa. Teknik pengambilan sampel menggunakan Simple Random Sampling. Uji hipotesis menggu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The critical thinking skills of students who are taught using the CTL model are better than those taught using the direct learning model. Furthermore, this research is also supported by Novitasari et al (2019b), They state that the critical thinking skills on ecosystem materials of students taught using the CTL were higher than those taught using conventional learning. Based on previous research, the CTL model assisted by Zoom Cloud Meeting has never been applied to influence critical thinking skills.…”
Section: Contextual Teaching and Learningsupporting
confidence: 58%
See 1 more Smart Citation
“…The critical thinking skills of students who are taught using the CTL model are better than those taught using the direct learning model. Furthermore, this research is also supported by Novitasari et al (2019b), They state that the critical thinking skills on ecosystem materials of students taught using the CTL were higher than those taught using conventional learning. Based on previous research, the CTL model assisted by Zoom Cloud Meeting has never been applied to influence critical thinking skills.…”
Section: Contextual Teaching and Learningsupporting
confidence: 58%
“…The critical thinking skills of students who were taught using the CTL model were better than those taught using the Direct Instruction model. Furthermore, Novitasari et al (2019a) state that the critical thinking skills on ecosystem materials of students taught using the CTL model were higher than those taught using the Direct Instruction model.…”
Section: Resultsmentioning
confidence: 95%
“…So that Sig.count > or 0.805 > 0.025 and 0.068 > 0.025, it can be concluded that H0 which states that the population is normally distributed is accepted and H1 which states that the population is not normally distributed is rejected. The homogeneity test aims to see whether the data in the two groups come from a homogeneous population (Novitasari et al, 2019;Sumardi Hr & Surianti, 2019). Based on the results of the analysis with the help of SPSS (Statistical Product and Service Solution) version 22.0, the value of Sig.…”
Section: Resultsmentioning
confidence: 99%